Psychological Well-Being Dynamics of Catholic Pastors in Surabaya - Bartolomeus Yofana Adiwena; Khanis Suvianita; Hartanti Hartanti (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2016)
Being a pastor is a challenging life calling, not only in terms of duties and responsibilities, but also due to the lifestyle “demands”. On a personal level, a pastor is an individual who still needs to take care of their own welfare as well as being cared for. The current study is a qualitative research that aims to understand the psychological well-being dynamics of pastors. There are two informants in this study. Results showed that factors supporting the psychological well-being of the two pastors are self-determination, skill and positive values acquired from the seminary, adaptive coping strategies, and social support.